If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -5) + -8 = 6 + 3(x + 2) Reorder the terms: 2(-5 + x) + -8 = 6 + 3(x + 2) (-5 * 2 + x * 2) + -8 = 6 + 3(x + 2) (-10 + 2x) + -8 = 6 + 3(x + 2) Reorder the terms: -10 + -8 + 2x = 6 + 3(x + 2) Combine like terms: -10 + -8 = -18 -18 + 2x = 6 + 3(x + 2) Reorder the terms: -18 + 2x = 6 + 3(2 + x) -18 + 2x = 6 + (2 * 3 + x * 3) -18 + 2x = 6 + (6 + 3x) Combine like terms: 6 + 6 = 12 -18 + 2x = 12 + 3x Solving -18 + 2x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -18 + 2x + -3x = 12 + 3x + -3x Combine like terms: 2x + -3x = -1x -18 + -1x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 -18 + -1x = 12 + 0 -18 + -1x = 12 Add '18' to each side of the equation. -18 + 18 + -1x = 12 + 18 Combine like terms: -18 + 18 = 0 0 + -1x = 12 + 18 -1x = 12 + 18 Combine like terms: 12 + 18 = 30 -1x = 30 Divide each side by '-1'. x = -30 Simplifying x = -30
| 2B=B-10 | | -2.1=y-4.2 | | 2x+5=14+7/3x | | 7y-5.9=8y | | (-3x^2+5)-(5x^2+2x-6)= | | 8(m-3)=36 | | 2x-5=4(x-3) | | 45=9-8x | | 5m+7m=24 | | 3x+2-7x-5=2x+9 | | 7.72x+16=59.5984+4x | | x^2-5x+19=0 | | 5-5n-4=11 | | r^2=24 | | x+2(5+3x)=87 | | 3x=5-4 | | 3x-5+2x=20 | | 12x+5=4x+3 | | 3x-3-4=5 | | r^2-24=0 | | 46+2x=6x+8x+10 | | 1.35m+0.03=7.80 | | y=100x+400 | | 4(6n-4)=128 | | 2m-5=37 | | 4x+18=6x-2 | | 2a+5(a+3)= | | -8(1-7n)=216 | | 3(7x+8)+6(4x+9)=213 | | 3-4(x+7)=13 | | 6x-10+4x+30=50 | | 2(x-7)+12=24 |